Strategi Bisnis Kewirausahaan Sosial ABC Periode 2021-2023 - Hastono, Diatrhi; Hidayati, Aprihatiningrum (Journal of Emerging Business Management and Entrepreneurship Studies, 2021)
ABC is a social enterprise that gives training and coaching for business and management also provide mentoring for orphans to start their own business and acting as the linkage between the market and the orphans’ products. Hence, ABC needs a platform such as marketplace by 2023. To achieve this target, ABC has to build business and functional strategies to make the target comes true. ABC does external analysis by using PESTEL, Porter’s Five Forces, Competitor Profile Matrix, and Decision-Making Process. The internal analysis held by using 7S McKinsey. ABC also analyze any impact and map the stakeholder priority.  Based on all the analysis, the business strategy for 2021 to 2023 was built and named as Strategi BANGUN. For 2021, ABC has to confirm its curriculum and the marketplace concept. In the next year, ABC has to build its management system and gain some external fundings. By the end of 2023, ABC has to launch its own marketplace. These strategies need be supported by the functional strategies to be achieved. If all the business strategies could be achieved, then ABC’s target to have its own marketplace by 2023 will be fulfilled.